Obtenção e caracterização de compósitos nanoestruturados de poli(sulfeto de fenileno) reforçados com nanotubos de carbono - Ribeiro, Bruno [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In this work, pristine and functionalized multiwalled carbon nanotubes reinforced poly (phenylene sulfide) composites were successfully obtained by melt mixing technique. The nanostructured composites were characterized by means of electrical, thermal, mechanical, rheological, and morphological methods. The electrical conductivity of neat PPS showed an increase by 11 and 9 orders of magnitude when 3.0 and 4.0 wt% of pristine MWCNT and functionalized MWCNT were incorporated in polymeric matrix, respectively. Moreover, the electrical percolation thresholds found on these systems were 2.1 and 3.6 wt%, suggesting the formation of three-dimensional conductive network within the polymeric matrix. The maximum crystallization temperature of PPS increased by about 19°C and 13°C due the incorporation of pristine (p-MWCNT) and functionalized filler (f- MWCNT), demonstrating the nucleating effect of the nanoparticles. Dynamic mechanical analysis showed an increase in storage modulus and glass transition temperature, due the incorporation of p-MWCNT and f-MWCNT in PPS matrix. However, it is worth to mention that the increment was bigger in p-MWCNT/PPS system. The maximum degradation temperature of PPS increased by about 14°C and 6°C due to the incorporation of 4,0 and 2,0 wt% of p-MWCNT and f-MWCNT, respectively, suggesting the formation of more thermally stable systems. The storage modulus (G’) of neat PPS presented an increase by 2 orders of magnitude when 2.0 and 3.0 wt% of pristine MWCNT and functionalized MWCNT were considered, with the formation of an interconnected nanotube structure, indicative of ‘pseudo-solid-like’ behavior. Percolation networks formed when the loading levels achieve up to 1.5 and 2.3 wt% for the composites with pristine MWCNT (p-MWCNT/PPS) and functionalized MWCNT (f-MWCNT/PPS), respectively. In addition, for ... (Complete abstract click electronic access below)

Neste trabalho, compósitos de poli(sulfeto de fenileno) reforçados com nanotubos de carbono (MWCNT) puros e funcionalizados foram obtidos a partir da técnica de mistura em fusão. Os compósitos nanoestruturados foram caracterizados através de ensaios elétricos, térmicos, mecânicos reológicos e morfológicos. A condutividade elétrica do PPS apresentou um aumento de 11 e 9 ordens de magnitude quando 3,0 e 4,0% em massa de MWCNT puros e funcionalizados foram incorporados na matriz polimérica, respectivamente. Além disso, os limites de percolação elétrica encontrado para esses sistemas foram de 2,1 e 3,6 m/m%, o que sugere a formação de uma rede tridimensional condutora no interior da matriz polimérica. A temperatura máxima de cristalização do PPS apresentou aumentos de 19°C e 13°C devido a incorporação dos reforços puros (p-MWCNT) e funcionalizados (f-MWCNT), respectivamente, evidenciando o efeito nucleante das nanopartículas. A análise dinâmico mecânica mostrou um aumento no módulo de armazenamento e na temperatura de transição vítrea a partir do aumento da concentração de MWCNT, com um incremento maior para o sistema p-MWCNT/PPS. A temperatura máxima de degradação do PPS aumentou 14°C e 6°C devido a incorporação de 4,0 e 2,0% em massa de p-MWCNT e f-MWCNT, respectivamente, sugerindo a formação de sistemas termicamente mais estáveis. O módulo de armazenamento (G’) do PPS apresentou um aumento de 2 ordens de magnitude quando 2,0 e 3,0% em massa de MWCNT puros e funcionalizados foram considerados, com a formação de uma estrutura interconectada de nanotubos, destacando o comportamento pseudoplástico das amostras. A formação de uma rede percolada de nanotubos foi atingida para concentrações de 1,5 e 2,3, m/m% em compósitos de p-MWCNT/PPS e f-MWCNT/PPS, respectivamente. As análises de microscopia ... (Resumo completo, clicar acesso eletrônico abaixo)
Preparation and characterization of carbon nanotubes reinforced poly(phenylene sulfide) composites
Keywords: Nanotubos de carbono; Materiais nanoestruturados; Polimerização; Compositos polimericos; Cristalização; Nanostructured materials